Positive pole piece, preparation method thereof, battery comprising positive pole piece and electric device
By forming a nickel salt particle coating on the core surface of the positive electrode active material of the secondary battery, the problems of structural stability and fast charging performance of high nickel positive electrode materials during circulation are solved, and high energy density and good cycle performance are improved. .
Patent Information
- Application Number
- CN202310810164.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-04
AI Technical Summary
During the circulation process of existing secondary batteries, there is a cation mixing phenomenon of high-nickel cathode materials, resulting in structural changes, increased stress, particle cracking and powdering, which deteriorates the circulation performance and fast charging performance.
Using nickel-containing lithium transition metal oxide as the core of the positive electrode active material, and forming a nickel salt particle coating on its surface, relieving stress through the lamination distribution of nickel salt particles, improving structural stability and ion transport capability, reducing and fast Risk of contact with high conductive liquid.
High energy density, good cycle performance and fast charging performance are achieved, while reducing the cost and production complexity of secondary batteries.
Smart Images

Figure CN119275248A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode plate and a preparation method thereof, a battery comprising the same, and an electrical device. Background Art
[0002] Secondary batteries rely on active ions to be reciprocated between the positive and negative electrodes for charging and discharging. Secondary batteries represented by lithium-ion batteries have outstanding features such as high energy density, long cycle life, no pollution, and no memory effect. Therefore, as a clean energy, secondary batteries have gradually spread from electronic products to large-scale devices such as electric vehicles to adapt to the sustainable development strategy of the environment and energy.
[0003] With the development of electronic products, electric vehicles and other devices, people have put forward higher requirements on the energy density and fast charging performance of secondary batteries. Summary of the invention
[0004] In order to achieve the above-mentioned objectives, the present application provides a positive electrode sheet, which can improve the energy density, cycle performance and fast charging performance of the battery containing it; the present application also provides a method for preparing the positive electrode sheet, a battery containing the positive electrode sheet and an electrical device.
[0005] The embodiment of the first aspect of the present application provides a positive electrode plate, which includes a positive electrode active material. The positive electrode active material includes: a core, including a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide; and a coating layer, which is coated on at least a portion of the surface of the core, and the coating layer includes nickel salt particles.
[0006] Without intending to be limited by any theory or explanation, the positive electrode plate of the embodiment of the present application includes the above-mentioned positive electrode active material, which can make the high-nickel positive electrode material system battery have high energy density, good cycle performance and good fast charging performance. Specifically, the core of the positive electrode active material includes the above-mentioned nickel-containing lithium transition metal oxide, that is, the high-nickel positive electrode material, which can make the positive electrode active material have a higher theoretical gram capacity, thereby allowing the battery to have a higher energy density. The coating layer of the positive electrode active material includes nickel salt particles. On the one hand, the nickel salt particles have a low nickel content, which not only has a high structural stability, but also is not easy to react violently with the fast-charging high-conductivity electrolyte, thereby delaying the contact between the high-nickel positive electrode material and the electrolyte; on the other hand, compared with the low-nickel ternary material layer in the related art, the coating layer containing nickel salt particles can withstand greater stress, thereby suppressing the cracking of the positive electrode active material particles during the cycle and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode plate of the embodiment of the present application can also effectively improve the cycle performance of the battery. In addition, nickel salt particles have good ion transport capabilities, which can enable the positive electrode active material to maintain good ion transport performance, thereby allowing the battery to have good fast charging performance.
[0007] In addition, compared with the low-nickel ternary positive electrode material in the related art, the nickel salt particles in the embodiment of the present application have low preparation cost and mature preparation process, which can also reduce the cost of secondary batteries and improve the production capacity of secondary batteries.
[0008] Therefore, the positive electrode plate of the embodiment of the present application is applied to a secondary battery, which can enable the battery to have high energy density, high production capacity, good cycle performance and good fast charging performance.
[0009] In any embodiment of the present application, based on the total mass of the core, the mass percentage of Ni in the core is w1%; based on the total mass of the coating layer, the mass percentage of Ni in the coating layer is w2%; the positive electrode active material satisfies: w2<w1. This helps to delay the contact between the core and the fast-charging high-conductivity electrolyte, thereby helping to improve the structural stability of the positive electrode active material during the fast charging process, and further improve the cycle performance and fast charging performance of the battery.
[0010] In any embodiment of the present application, the coating layer includes a plurality of nickel salt particle layers stacked and distributed in a direction away from the core.
[0011] Optionally, among the multiple nickel salt particle layers, the mass percentage of the Ni element in the nickel salt particle layer far away from the core is less than the mass percentage of the Ni element in the nickel salt particle layer close to the core.
[0012] When the coating layer includes the above-mentioned multiple nickel salt particle layers, the multiple nickel salt particle layers can release the stress accumulated in the inner core during the cycle. In particular, when the mass percentage of the Ni element in the multiple nickel salt particle layers decreases successively in the direction away from the inner core, the multiple nickel salt particle layers can also slowly release the stress layer by layer. As a result, the risk of cracking of the positive electrode active material particles can be significantly reduced, thereby delaying the contact between the inner core and the fast-charging high-conductivity electrolyte, and reducing the risk of pulverization and deactivation of high-nickel positive electrode materials.
[0013] In any embodiment of the present application, the thickness of the coating layer is 100 nm-5 μm, and can be optionally 200 nm-900 nm.
[0014] In any embodiment of the present application, the volume distribution particle size Dv50 of the inner core is 1.2 μm-15 μm, and can be optionally 10 μm-15 μm.
[0015] When the thickness of the coating layer and / or the volume distribution particle size Dv50 of the inner core meets the given range, it can not only effectively delay the contact between the inner core and the fast-charging high-conductivity electrolyte, but also enable the positive electrode active material to have a higher theoretical gram capacity.
[0016] In any embodiment of the present application, the volume distribution particle size Dv50 of the nickel salt particles is 50nm-500nm, and can be optionally 50nm-200nm.
[0017] When the volume distribution particle size Dv50 of the nickel salt particles meets the given range, on the one hand, it helps to form a dense coating layer, thereby delaying the contact between the inner core and the fast-charging and high-conductivity electrolyte, which in turn helps to improve the cycle performance of the battery; on the other hand, it helps to reduce the pores between the positive electrode active material particles in the positive electrode sheet, thereby increasing the compaction density of the positive electrode film layer, which in turn helps to improve the energy density of the battery.
[0018] In any embodiment of the present application, the nickel-containing lithium transition metal oxide includes LiNi x Co y Mn z O 2 , wherein 0.7≤x<1.0, 0<y<0.3, 0<z<0.3. Thus, the secondary battery can have both high energy density and good cycle performance.
[0019] In any embodiment of the present application, the nickel salt particles include oxoacid salts of nickel.
[0020] Optionally, the nickel salt particles include at least one of nickel acetate, nickel silicate or nickel carbonate.
[0021] The above-mentioned types of nickel salt particles have a lower nickel content and good ion transport capability, thereby improving the cycle performance and fast charging performance of the battery.
[0022] In any embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, and the positive electrode active material is distributed in the positive electrode film layer. The compaction density of the positive electrode film layer is greater than or equal to 3.6 g / cm 3 , optional 3.6g / cm 3 -4.6g / cm 3 As a result, the positive electrode active material particles in the positive electrode film layer can be brought into close contact, increasing the positive electrode active material content per unit volume, thereby allowing the secondary battery to have a higher energy density.
[0023] The embodiment of the second aspect of the present application provides a method for preparing a positive electrode plate, comprising: providing an initial positive electrode plate, the initial positive electrode plate comprising initial positive electrode particles, the initial positive electrode particles comprising a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of the transition metal element in the nickel-containing lithium transition metal oxide; immersing the initial positive electrode plate in a nickel salt solution and drying it to form a coating layer comprising nickel salt particles on at least a portion of the surface of the initial positive electrode particles, thereby obtaining a positive electrode plate. The positive electrode plate comprises a positive electrode active material, the positive electrode active material comprising: an inner core comprising a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of the transition metal element in the nickel-containing lithium transition metal oxide; and a coating layer, coating at least a portion of the surface of the inner core, the coating layer comprising nickel salt particles.
[0024] According to the method of the embodiment of the present application, the prepared positive electrode plate includes the above-mentioned positive electrode active material, which can make the high-nickel positive electrode material system battery have high energy density, good cycle performance and good fast charging performance. Specifically, the core of the positive electrode active material includes the above-mentioned nickel-containing lithium transition metal oxide, that is, the high-nickel positive electrode material, which can make the positive electrode active material have a higher theoretical gram capacity, thereby allowing the battery to have a higher energy density. The coating layer of the positive electrode active material includes nickel salt particles. On the one hand, the nickel salt particles have a low nickel content, which not only has a high structural stability, but also is not easy to react violently with the fast-charging high-conductivity electrolyte, thereby delaying the contact between the high-nickel positive electrode material and the electrolyte; on the other hand, compared with the low-nickel ternary material layer in the related art, the coating layer containing nickel salt particles can withstand greater stress, thereby suppressing the cracking of the positive electrode active material particles during the cycle and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode plate of the embodiment of the present application can also effectively improve the cycle performance of the battery. In addition, nickel salt particles have good ion transport capabilities, which can enable the positive electrode active material to maintain good ion transport performance, thereby allowing the battery to have good fast charging performance.
[0025] In addition, the method according to the embodiment of the present application forms a coating layer including nickel salt particles on at least part of the surface of the initial positive electrode particles by impregnation, which is not only simple to operate and has low production cost, but also can improve the compaction density of the positive electrode film layer. Thus, the production capacity and energy density of the secondary battery can also be improved.
[0026] Therefore, the positive electrode sheet prepared according to the method of the embodiment of the present application is applied to a secondary battery, which can effectively improve the energy density, production capacity, cycle performance and fast charging performance of the battery.
[0027] In any embodiment of the present application, the initial positive electrode plate is immersed in a nickel salt solution and dried, including: the initial positive electrode plate is immersed in multiple nickel salt solutions in turn and dried to form multiple stacked nickel salt particle layers on at least a portion of the surface of the initial positive electrode particles.
[0028] Optionally, in the multiple nickel salt solutions, the mass percentage of the Ni element decreases in sequence based on the total mass of the solid components in the nickel salt solutions.
[0029] The above-mentioned embodiment can form a plurality of stacked nickel salt particle layers on at least part of the surface of the initial positive electrode particles. Thus, during the charge and discharge cycle, the plurality of nickel salt particle layers can release the accumulated stress in the inner core. In particular, when the mass percentage of the Ni element in the plurality of nickel salt particle layers decreases successively in the direction away from the inner core, the plurality of nickel salt particle layers can also release the stress slowly layer by layer. Thus, the risk of cracking of the positive electrode active material particles can be significantly reduced, thereby delaying the contact between the inner core and the fast-charging high-conductivity electrolyte, and reducing the risk of pulverization and deactivation of the high-nickel positive electrode material.
[0030] In any embodiment of the present application, the molar concentration of the Ni element in the nickel salt solution is 0.05 mol / L-0.6 mol / L, which helps to form nickel salt particles of suitable particle size and a nickel salt particle layer of suitable thickness on the surface of the initial positive electrode particles.
[0031] In any embodiment of the present application, based on the total mass of the solid components in the nickel salt solution, the mass percentage of the Ni element is 5%-60%. When the mass percentage of the Ni element meets the given range, the coating layer can have a suitable Ni element content, so that the coating layer maintains good structural stability during the charge and discharge cycle of the battery.
[0032] In any embodiment of the present application, in the nickel salt solution, the solid component includes nickel salt and optional additives.
[0033] Optionally, the optional additives include a binder and / or a conductive agent;
[0034] More optionally, the binder includes an aqueous binder; and the conductive agent includes a conductive carbon material.
[0035] This helps to form a coating layer having an appropriate thickness and an appropriate Ni element content.
[0036] In any embodiment of the present application, the initial positive electrode sheet includes a positive electrode current collector and an initial positive electrode film layer located on at least one side of the positive electrode current collector, and the compaction density of the initial positive electrode film layer is 3.1 g / cm 3 -4.1g / cm 3 Thus, the prepared positive electrode sheet can have a higher compaction density, thereby allowing the secondary battery to have a high energy density.
[0037] The third aspect of the present application provides a battery, comprising the positive electrode sheet of the first aspect, or the positive electrode sheet prepared according to the method of the second aspect. The battery can at least have high energy density, good cycle performance and good fast charging performance.
[0038] In any embodiment of the present application, the battery cell further comprises an electrolyte, and the ion conductivity of the electrolyte at 25° C. is greater than 10 mS / cm, and can be selected to be 10 mS / cm-18 mS / cm. This allows the battery to have good fast charging performance.
[0039] An embodiment of a fourth aspect of the present application provides an electrical device, comprising the battery of the third aspect.
[0040] The electric device according to the embodiment of the present application comprises the battery of the third aspect, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the structure of the positive electrode active material in one embodiment of the present application.
[0042] Figure 2 It is a schematic diagram of an implementation of a battery cell of the present application.
[0043] Figure 3 yes Figure 2 An exploded view of an embodiment of a battery cell of the present application is shown.
[0044] Figure 4 It is a schematic diagram of an embodiment of a battery module of the present application.
[0045] Figure 5 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0046] Figure 6 yes Figure 5 An exploded view of an embodiment of a battery pack of the present application is shown.
[0047] Figure 7 It is a schematic diagram of an implementation of an electrical device of the present application, and the electrical device may include a battery pack or a battery module according to an embodiment of the present application as a power source.
[0048] 10 positive electrode active material; 11 inner core; 12 coating layer; 12a nickel salt particle layer; 1 battery pack; 2 upper box body; 3 lower box body; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0049] Hereinafter, the embodiments of the positive electrode sheet and the method for preparing the same, the battery and the electric device containing the same are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0055] Unless otherwise specified, the ratio parameters involved in this application are compared in the same unit. For example, the thickness ratio of A to B is 1.2:1, and the thickness units of A and B are the same.
[0056] With the development of electronic products, electric vehicles and other devices, people have put forward higher requirements on the energy density and fast charging performance of secondary batteries.
[0057] High-nickel positive electrode materials, such as lithium transition metal oxides in which the molar ratio of Ni in transition metal elements is above 0.7, have become a research hotspot for high energy density battery systems in recent years due to their advantages such as high reversible capacity and low cost. However, secondary batteries in high-nickel positive electrode material systems will experience a relatively serious cation mixing phenomenon during the cycle process. The cation mixing phenomenon will cause irreversible phase changes in the high-nickel positive electrode material, thereby aggravating the changes in the crystal structure of the high-nickel positive electrode material, resulting in increased stress inside the high-nickel positive electrode material particles, inducing microcracks, and increasing the risk of cracking, pulverization, and deactivation of the high-nickel positive electrode material particles, thereby deteriorating the battery's cycle performance.
[0058] In addition, when faced with the need for fast charging performance, secondary batteries usually use electrolytes with high conductivity (i.e., fast-charging high-conductivity electrolytes). High-nickel positive electrode materials tend to react violently with fast-charging high-conductivity electrolytes. This exacerbates the irreversible capacity loss of high-nickel positive electrode materials and further deteriorates the battery's cycle performance.
[0059] In view of this, an embodiment of the present application provides a positive electrode plate, which can enable a battery containing the positive electrode plate to have high energy density, good cycle performance and good fast charging performance; the present application also provides a method for preparing the positive electrode plate, a battery containing the positive electrode plate, and an electrical device.
[0060] Positive electrode
[0061] The embodiment of the first aspect of the present application proposes a positive electrode plate, which includes a positive electrode active material. The positive electrode active material includes a core and a coating layer, and the coating layer is coated on at least a portion of the surface of the core. The core includes a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide; and the coating layer includes nickel salt particles.
[0062] After in-depth research, it was found that delaying the contact between high-nickel positive electrode materials and fast-charging high-conductivity electrolytes and maintaining good ion transmission capabilities of high-nickel positive electrode materials is one of the effective means to improve the cycle performance and fast charging performance of batteries with high-nickel positive electrode material systems. The relevant technology involves repeatedly coating low-nickel ternary positive electrode material layers on the surface of high-nickel ternary positive electrode material particles to obtain a composite positive electrode material with an inner layer of high-nickel ternary positive electrode material and an outer layer of low-nickel ternary positive electrode material. However, on the one hand, the production of such a composite positive electrode material is time-consuming, labor-intensive, and costly; on the other hand, during the charge and discharge cycle of the battery, the stress generated by the high-nickel ternary positive electrode material easily causes the low-nickel ternary positive electrode material layer to rupture, resulting in very limited improvements in the battery's cycle performance and fast charging performance.
[0063] Without intending to be limited by any theory or explanation, the positive electrode plate of the embodiment of the present application includes the above-mentioned positive electrode active material, which can make the high-nickel positive electrode material system battery have high energy density, good cycle performance and good fast charging performance. Specifically, the core of the positive electrode active material includes the above-mentioned nickel-containing lithium transition metal oxide, that is, the high-nickel positive electrode material, which can make the positive electrode active material have a higher theoretical gram capacity, thereby allowing the battery to have a higher energy density. The coating layer of the positive electrode active material includes nickel salt particles. On the one hand, the nickel salt particles have a low nickel content, which not only has a high structural stability, but also is not easy to react violently with the fast-charging high-conductivity electrolyte, thereby delaying the contact between the high-nickel positive electrode material and the electrolyte; on the other hand, compared with the low-nickel ternary material layer in the related art, the coating layer containing nickel salt particles can withstand greater stress, thereby suppressing the cracking of the positive electrode active material particles during the cycle and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode plate of the embodiment of the present application can also effectively improve the cycle performance of the battery. In addition, nickel salt particles have good ion transport capabilities, which can enable the positive electrode active material to maintain good ion transport performance, thereby allowing the battery to have good fast charging performance.
[0064] In addition, compared with the low-nickel ternary positive electrode material in the related art, the nickel salt particles in the embodiment of the present application have low preparation cost and mature preparation process, which can also reduce the cost of secondary batteries and improve the production capacity of secondary batteries.
[0065] Therefore, the positive electrode plate of the embodiment of the present application is applied to a secondary battery, which can enable the battery to have high energy density, high production capacity, good cycle performance and good fast charging performance.
[0066] In an embodiment of the present application, the nickel-containing lithium transition metal oxide may adopt one or more of the nickel-containing lithium transition metal oxides and their modified compounds for secondary batteries known in the art. Examples of nickel-containing lithium transition metal oxides may include, but are not limited to, one or more of lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds with a nickel content of more than 0.7. The above-mentioned "nickel content is more than 0.7" may mean that the molar content of the Ni element is greater than or equal to 0.7 based on the total molar amount of the transition metal elements in the nickel-containing lithium transition metal oxide. For example, for lithium nickel cobalt manganese oxide, "nickel content is more than 0.7" may mean that the molar amount of the Ni element / (molar amount of the Ni element + molar amount of the Co element + molar amount of the Mn element) ≥ 0.7.
[0067] The structure of the positive electrode active material included in the positive electrode sheet provided in the embodiment of the present application can be characterized by equipment and methods known in the art. For example, the positive electrode active material particles can be subjected to argon ion cross-section polishing, the polished cross-section of the positive electrode active material particles can be observed by a scanning electron microscope (SEM), and the cross-section EDS element surface distribution map of the positive electrode active material particles can be measured by an EDS spectrometer. According to the distribution of the Ni element in the EDS element surface distribution map, the structure of the positive electrode active material can be determined.
[0068] In some embodiments, based on the total mass of the core, the mass percentage of Ni element in the core is w1%; based on the total mass of the coating layer, the mass percentage of Ni element in the coating layer is w2%; the positive electrode active material may satisfy: w2<w1.
[0069] Without intending to be bound by any theory or explanation, when the coating layer has a lower Ni content, it can maintain good structural stability during the charge and discharge cycle of the battery, thereby helping to delay the contact between the core and the fast-charge high-conductivity electrolyte, thereby helping to improve the structural stability of the positive electrode active material during the fast-charge process, and further improving the battery's cycle performance and fast-charge performance.
[0070] w1 and w2 have well-known meanings in the art and can be determined by equipment and methods known in the art. For example, w1 and w2 can be determined based on the EDS element surface distribution diagram of the positive electrode active material. The EDS element surface distribution diagram of the positive electrode active material can be obtained by the method described above, which will not be described in detail here.
[0071] In some embodiments, the coating layer may include a plurality of nickel salt particle layers stacked and distributed in a direction away from the core. Figure 1 Schematic diagram of the structure of the positive electrode active material of one embodiment of the present application. Figure 1 As shown, the positive electrode active material 10 may include a core 11 and a coating layer 12. The coating layer 12 may coat at least a portion of the surface of the core 11. The coating layer 12 may include a plurality of nickel salt particle layers 12a stacked and distributed in a direction away from the core.
[0072] The embodiment of the present application does not impose any specific limitation on the mass percentage of the Ni element in the multiple nickel salt particle layers.
[0073] In some embodiments, along the direction away from the inner core, the mass percentage of the Ni element in the innermost nickel salt particle layer is greater than the mass percentage of the Ni element in the outermost nickel salt particle layer.
[0074] Optionally, in some embodiments, among the multiple nickel salt particle layers, the mass percentage of Ni element in the nickel salt particle layer far from the core is less than the mass percentage of Ni element in the nickel salt particle layer close to the core. For example, the coating layer includes multiple nickel salt particle layers stacked and distributed in a direction away from the core, and any two nickel salt particle layers can satisfy: a <w b , w a % represents the mass percentage of Ni element in the nickel salt particle layer relatively far away from the core direction, w b % represents the mass percentage of Ni element in the nickel salt particle layer relatively close to the core.
[0075] Without intending to be limited to any theory or explanation, when the coating layer includes the above-mentioned multiple nickel salt particle layers, the multiple nickel salt particle layers can release the stress accumulated in the inner core during the cycle. In particular, when the mass percentage of the Ni element in the nickel salt particle layer away from the inner core is less than the mass percentage of the Ni element in the nickel salt particle layer close to the inner core, the multiple nickel salt particle layers can also release the stress slowly layer by layer. As a result, the risk of cracking of the positive electrode active material particles can be significantly reduced, thereby delaying the contact between the inner core and the fast-charging high-conductivity electrolyte, and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode sheet of the embodiment of the present application is applied to secondary batteries, which can significantly improve the cycle performance and fast charging performance of the battery.
[0076] In some embodiments, the thickness of the coating layer can be 100 nm-5 μm, for example, 100 nm, 110 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 500 nm, 1 μm, 2 μm, 4 μm, 5 μm, or a range consisting of any two of the above values.
[0077] Optionally, in some embodiments, the thickness of the coating layer may also be 200nm-900nm, for example, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, or a range consisting of any two of the above values.
[0078] In some embodiments, the volume distribution particle size Dv50 of the inner core may be 1.2 μm-15 μm, for example, 1.2 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 15 μm, or a range consisting of any two of the above values.
[0079] Optionally, in some embodiments, the volume distribution particle size Dv50 of the inner core can also be 10 μm-15 μm, for example, it can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two of the above values.
[0080] Without intending to be limited by any theory or explanation, when the thickness of the coating layer and / or the volume distribution particle size Dv50 of the core meets the given range, it can not only effectively delay the contact between the core and the fast-charge high-conductivity electrolyte, but also allow the positive electrode active material to have a higher theoretical gram capacity. Therefore, the positive electrode sheet of the embodiment of the present application is applied to the secondary battery, which can not only make the battery have good cycle performance and good fast charging performance, but also allow the battery to have a higher energy density.
[0081] The thickness of the coating layer and the volume distribution particle size Dv50 of the core material have well-known meanings in the art and can be measured by equipment and methods known in the art. As an example, it can be tested by the following method: randomly select an area in the positive electrode sheet, make a cross section parallel to the thickness direction of the positive electrode sheet, perform argon ion cross section polishing, and take an electron microscope (SEM image) with a magnification of 3000 times or more (for example, 3000 times or 5000 times); process the SEM image and adjust the appropriate contrast until the outline of the positive electrode active material particles can be clearly seen; use software to count the thickness of the coating layer and the core particle size in each positive electrode active material particle in the cross section, and calculate the thickness of the coating layer and the volume distribution particle size Dv50 of the core. As another example, it is also possible to sample from the positive electrode sheet to obtain a positive active material powder, directly perform argon ion cross section polishing on the positive active material powder, and take an SEM image, and determine the thickness of the coating layer and the volume distribution particle size Dv50 of the core through the SEM image.
[0082] In some embodiments, the volume distribution particle size Dv50 of the nickel salt particles can be 50nm-500nm, for example, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, or a range consisting of any two of the above values.
[0083] Optionally, in some embodiments, the volume distribution particle size Dv50 of the nickel salt particles can also be 50nm-200nm, for example, it can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, or a range consisting of any two of the above values.
[0084] Without intending to be limited by any theory or explanation, when the volume distribution particle size Dv50 of the nickel salt particles meets the given range, on the one hand, it helps to form a dense coating layer, thereby delaying the contact between the inner core and the fast-charging and high-conductivity electrolyte, thereby helping to improve the cycle performance of the battery; on the other hand, it helps to reduce the pores between the positive electrode active material particles in the positive electrode sheet, thereby increasing the compaction density of the positive electrode film layer, thereby helping to improve the energy density of the battery.
[0085] The volume distribution particle size Dv50 of the nickel salt particles has a well-known meaning in the art and can be measured by equipment and methods known in the art. As an example, it can be tested by the following method: randomly select an area in the positive electrode sheet, make a cross section parallel to the thickness direction of the positive electrode sheet, perform argon ion cross section polishing, and take an electron microscope (SEM image) with a magnification of 5000 times or more (for example, it can be 5000 times-20000 times); process the SEM image and adjust the appropriate contrast until the outline of the nickel salt particles in the coating layer can be clearly seen; use software to count the particle size of the nickel salt particles in the cross section, and determine the volume distribution particle size Dv50 of the nickel salt particles based on the statistical results.
[0086] In some embodiments, the nickel-containing lithium transition metal oxide may include LiNi x Co y Mn z O 2 , where 0.7≤x<1.0, 0<y<0.3, 0<z<0.3.
[0087] Without intending to be limited by any theory or explanation, in the positive electrode sheet of the embodiment of the present application, the positive electrode active material has a specific structure, which can make the core have better structural stability when it has a higher Ni content. When the nickel-containing lithium transition metal oxide contained in the core includes the above-mentioned high-nickel ternary positive electrode material, it can allow the secondary battery to have both high energy density and good cycle performance.
[0088] It should be noted that the ratio of each element in the nickel-containing lithium transition metal oxide in the present application refers to the ratio of each element in the core before the positive electrode active material is made into a positive electrode sheet and assembled into a battery for formation. Those skilled in the art can understand that in the positive electrode sheet, battery or electrical device, due to the formation and circulation processes, some elements will be consumed. Even if the measured element ratio in the core is not within the above range, it should fall within the scope of the present application. For example, since the battery undergoes formation and circulation processes, lithium ions will be consumed, so the measured lithium content in the core will be less than 1. At the same time, if the positive electrode sheet and the negative electrode sheet are supplemented with lithium, the measured lithium content in the core will be greater than 1 after the battery undergoes formation and circulation processes. In addition, since the battery undergoes circulation processes, the oxygen element in the core may be lost, so the measured oxygen content in the core will be less than 2.
[0089] In some embodiments, the nickel salt particles may include oxoacid salts of nickel.
[0090] Alternatively, in some embodiments, the nickel salt particles may include at least one of nickel acetate, nickel silicate, or nickel carbonate.
[0091] Without intending to be limited by any theory or explanation, the above-mentioned types of nickel salt particles have a lower nickel content, which not only has a higher structural stability, but also is not easy to react violently with the fast-charging high-conductivity electrolyte, thereby delaying the contact between the high-nickel positive electrode material and the electrolyte and improving the battery's cycle performance. In addition, the above-mentioned types of nickel salt particles also have good ion transport capabilities, which can enable the positive electrode active material to maintain good ion transport performance, thereby allowing the battery to have good fast charging performance.
[0092] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, and the positive electrode active material is distributed in the positive electrode film layer. The compaction density of the positive electrode film layer may be greater than or equal to 3.6 g / cm 3 , optional 3.6g / cm 3 -4.6g / cm 3 .
[0093] In the positive electrode sheet of the embodiment of the present application, the positive electrode active material has a specific structure, so that the positive electrode film layer can have a higher compaction density. As a result, the positive electrode active material particles in the positive electrode film layer can be closely contacted, and the positive electrode active material content per unit volume is increased, thereby allowing the secondary battery to have a higher energy density.
[0094] The compaction density of the positive electrode film layer has a meaning well known in the art, and can be tested using equipment and methods known in the art. The compaction density of the positive electrode film layer = the surface density of the positive electrode film layer / the thickness of the single-sided positive electrode film layer. The surface density of the positive electrode film layer has a meaning well known in the art, and can be tested using equipment and methods known in the art, such as taking a single-sided coated and cold-pressed positive electrode pole piece (if it is a double-sided coated positive electrode pole piece, the positive electrode film layer on one side can be wiped off first), punching it into small discs, and weighing it; then wipe off the positive electrode film layer of the weighed positive electrode pole piece, and weigh the weight of the current collector. The surface density of the positive electrode film layer = (weight of the small disc - weight of the current collector) / area of the small disc.
[0095] In the embodiment of the present application, the positive electrode sheet may include a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0096] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0097] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0098] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0099] Preparation method
[0100] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising the following steps S10 to S20.
[0101] S10, providing an initial positive electrode plate, the initial positive electrode plate comprising initial positive electrode particles, the initial positive electrode particles comprising a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide.
[0102] In step S10, the initial positive electrode sheet can be prepared by a method known in the art, which is not limited here. As an example, the positive electrode slurry can be coated on the positive electrode collector, dried, cold pressed, and a positive electrode film layer is formed on the surface of the positive electrode collector to obtain the initial positive electrode sheet. The positive electrode slurry can be formed by dispersing the above-mentioned nickel-containing lithium transition metal oxide, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0103] S20, immersing the initial positive electrode sheet in a nickel salt solution and drying it to form a coating layer including nickel salt particles on at least a portion of the surface of the initial positive electrode particles to obtain a positive electrode sheet.
[0104] In step S20, the nickel salt particles may include the nickel salt particles described in the first aspect. The embodiments of the nickel salt particles have been described and illustrated in detail above and will not be repeated here. The nickel salt solution can be obtained by dissolving the nickel salt particles in a solvent, as long as the solvent can dissolve the nickel salt particles. When the nickel salt particles are specific substances, those skilled in the art can select appropriate solvents according to actual needs, which are not limited here. In some embodiments, the nickel salt particles used to prepare the nickel salt solution have a volume distribution particle size Dv50 of 50nm-500nm.
[0105] Step S20 can form a coating layer on the surface of the initial positive electrode particles by impregnation, and the gaps between the initial positive electrode particles can be filled with nickel salt particles to form a dense protective film on the surface of the initial positive electrode particles, thereby effectively delaying the contact between the initial positive electrode particles and the fast-charging high-conductivity electrolyte. In addition, by filling the gaps between the initial positive electrode particles with nickel salt particles, the compaction density of the initial positive electrode film layer can also be increased, thereby increasing the energy density of the positive electrode sheet.
[0106] The positive electrode sheet prepared according to steps S10 and S20 includes a positive electrode active material, the positive electrode active material includes a core and a coating layer, and the coating layer is coated on at least a portion of the surface of the core. The core includes a nickel-containing lithium transition metal oxide, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide; and the coating layer includes nickel salt particles.
[0107] According to the method of the embodiment of the present application, the prepared positive electrode plate includes the above-mentioned positive electrode active material, which can make the high-nickel positive electrode material system battery have high energy density, good cycle performance and good fast charging performance. Specifically, the core of the positive electrode active material includes the above-mentioned nickel-containing lithium transition metal oxide, that is, the high-nickel positive electrode material, which can make the positive electrode active material have a higher theoretical gram capacity, thereby allowing the battery to have a higher energy density. The coating layer of the positive electrode active material includes nickel salt particles. On the one hand, the nickel salt particles have a low nickel content, which not only has a high structural stability, but also is not easy to react violently with the fast-charging high-conductivity electrolyte, thereby delaying the contact between the high-nickel positive electrode material and the electrolyte; on the other hand, compared with the low-nickel ternary material layer in the related art, the coating layer containing nickel salt particles can withstand greater stress, thereby suppressing the cracking of the positive electrode active material particles during the cycle and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode plate of the embodiment of the present application can also effectively improve the cycle performance of the battery. In addition, nickel salt particles have good ion transport capabilities, which can enable the positive electrode active material to maintain good ion transport performance, thereby allowing the battery to have good fast charging performance.
[0108] In addition, the method according to the embodiment of the present application forms a coating layer including nickel salt particles on at least part of the surface of the initial positive electrode particles by impregnation, which is not only simple to operate and has low production cost, but also can improve the compaction density of the positive electrode film layer. Thus, the production capacity and energy density of the secondary battery can also be improved.
[0109] Therefore, the positive electrode sheet prepared according to the method of the embodiment of the present application is applied to a secondary battery, which can effectively improve the energy density, production capacity, cycle performance and fast charging performance of the battery.
[0110] In some embodiments, the initial positive electrode plate is immersed in a nickel salt solution and dried, which may specifically include: immersing the initial positive electrode plate in multiple nickel salt solutions in turn and drying them to form multiple stacked nickel salt particle layers on at least a portion of the surface of the initial positive electrode particles.
[0111] Optionally, in the multiple nickel salt solutions, the mass percentage of the Ni element decreases in sequence based on the total mass of the solid components in the nickel salt solutions. Thus, in the coating layer of the positive electrode active material, the mass percentage of the Ni element in the multiple nickel salt particle layers decreases in sequence in the direction away from the core.
[0112] In the embodiments of the present application, the time of impregnation is not specifically limited, and those skilled in the art can adjust it according to actual needs. As an example, the time of each impregnation can be 2h-48h. The time and temperature of drying are not specifically limited, and those skilled in the art can adjust it according to actual needs. As an example, the time of each drying can be 2h-48h, and the drying temperature can be 80℃-120℃.
[0113] In the above embodiment, by immersing the initial positive electrode plate in a plurality of nickel salt solutions in turn and drying them, a plurality of nickel salt particle layers distributed in a stacked manner can be formed on at least a portion of the surface of the initial positive electrode particles. Thus, during the charge and discharge cycle, the plurality of nickel salt particle layers can release the accumulated stress in the inner core. In particular, when the mass percentage of the Ni element in the plurality of nickel salt particle layers decreases successively in the direction away from the inner core, the plurality of nickel salt particle layers can also release the stress slowly layer by layer. Thus, the risk of cracking of the positive electrode active material particles can be significantly reduced, thereby delaying the contact between the inner core and the fast-charging high-conductivity electrolyte, and reducing the risk of pulverization and inactivation of the high-nickel positive electrode material. Therefore, the positive electrode plate prepared in the embodiment of the present application is applied to a secondary battery, which can significantly improve the cycle performance and fast charging performance of the battery.
[0114] In some embodiments, the molar concentration of Ni element in the nickel salt solution may be 0.05 mol / L-0.6 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, or a range consisting of any two of the above values.
[0115] Without intending to be limited by any theory or explanation, when the molar concentration of the Ni element in the nickel salt solution is within the above-mentioned suitable range, it helps to form nickel salt particles of suitable particle size on the surface of the initial positive electrode particles, and to form a nickel salt particle layer of suitable thickness.
[0116] In some embodiments, based on the total mass of the solid components in the nickel salt solution, the mass percentage of the Ni element can be 5%-60%, for example, 5%, 10%, 20%, 30%, 40%, 50%, 60%, or a range consisting of any two of the above values.
[0117] When the mass percentage of the Ni element meets the given range, the coating layer can have a suitable Ni element content, so that the coating layer maintains good structural stability during the charge and discharge cycle of the battery. This helps to delay the contact between the core and the fast-charge high-conductivity electrolyte, thereby helping to improve the structural stability of the positive electrode active material during the fast charging process, and further improve the battery's cycle performance and fast charging performance.
[0118] In some embodiments, in the nickel salt solution, the solid component may include a nickel salt and optional additives.
[0119] Optionally, the optional additives include a binder and / or a conductive agent.
[0120] More optionally, the binder may include an aqueous binder. An aqueous binder generally refers to a binder that can use water as a dispersant or solvent. Examples of aqueous binders may include one or more aqueous binders known in the art, such as aqueous polyvinylidene fluoride (PVDF) and its derivatives, polyacrylic acid and its derivatives, acrylonitrile multipolymers, sodium alginate and its derivatives, polyacrylate and its derivatives, at least one of which is not limited here. In some embodiments, the aqueous binder may include aqueous PVDF.
[0121] The conductive agent may include a conductive carbon material. For example, it may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, and Ketjen black. In some embodiments, the aqueous binder may include Ketjen black.
[0122] This helps to form a coating layer having an appropriate thickness and an appropriate Ni element content.
[0123] In some embodiments, the initial positive electrode sheet includes a positive electrode current collector and an initial positive electrode film layer located on at least one side of the positive electrode current collector. The compaction density of the initial positive electrode film layer may be 3.1 g / cm 3 -4.1g / cm 3 Thus, the prepared positive electrode sheet can have a higher compaction density, thereby allowing the secondary battery to have a high energy density.
[0124] Battery
[0125] The battery mentioned in the embodiments of the present application may include one or more battery cells to provide a single physical module with higher voltage and capacity. When there are multiple battery cells, the multiple battery cells are connected in series, in parallel or in mixed connection through a busbar component.
[0126] Typically, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, which can prevent the positive and negative electrodes from short-circuiting and allow active ions to pass through. The electrolyte plays the role of conducting active ions between the positive electrode plate and the negative electrode plate.
[0127] [Positive electrode]
[0128] In the battery cell of the embodiment of the present application, the positive electrode sheet of the electrode assembly may include the positive electrode sheet of the first aspect or the positive electrode sheet prepared according to the method of the second aspect. The embodiments of the positive electrode sheet have been described and illustrated in detail above, and will not be repeated here. It can be understood that the battery cell of the embodiment of the present application can achieve the beneficial effects of any of the above embodiments of the positive electrode sheet of the embodiment of the present application.
[0129] [Negative electrode]
[0130] The negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0131] The negative electrode active material may adopt the negative electrode active material for secondary batteries known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material.
[0132] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0133] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0134] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC-Na), a PTC thermistor material, and the like.
[0135] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0136] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0137] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0138] [Isolation film]
[0139] The separator is disposed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The embodiment of the present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0140] In some embodiments, the material of the isolation membrane can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different, without special restrictions.
[0141] [Electrolytes]
[0142] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid or gel.
[0143] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0144] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0145] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0146] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0147] In some embodiments, the ionic conductivity of the electrolyte at 25° C. may be greater than 10 mS / cm, and may be 10 mS / cm-18 mS / cm. This allows the battery to have good fast charging performance.
[0148] The ionic conductivity of the electrolyte has a well-known meaning in the art and can be measured by equipment and methods known in the art, for example, by using a conductivity meter with reference to HG / T 4066-4067-2008.
[0149] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0150] In some embodiments, the battery cell further includes a housing for accommodating the electrode assembly and the electrolyte. The housing of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The housing of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0151] The embodiment of the present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0152] In some embodiments, reference Figure 3 , the shell may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0153] The preparation method of the battery cell of the embodiment of the present application is well known. In some embodiments, the electrode assembly can be placed in a housing, and after drying, an electrolyte can be injected, and the battery cell can be obtained through vacuum packaging, standing, forming, shaping and other processes.
[0154] In some embodiments, the battery mentioned in the embodiments of the present application refers to a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the embodiments of the present application can be a battery module or a battery pack. The battery generally includes a box for encapsulating one or more battery cells. The box can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells.
[0155] In some embodiments, there may be multiple battery cells in the battery, and the multiple battery cells may be connected in series, in parallel, or in a hybrid connection. A hybrid connection means that the multiple battery cells are both connected in series and in parallel. The multiple battery cells may be directly connected in series, in parallel, or in a hybrid connection, and then the whole formed by the multiple battery cells is accommodated in the box; of course, multiple battery cells may be first connected in series, in parallel, or in a hybrid connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in a hybrid connection to form a whole, and then accommodated in the box.
[0156] Figure 4 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 4 As shown, there are multiple battery cells 5, and the multiple battery cells 5 are first connected in series, in parallel, or in mixed connection to form a battery module 4. The multiple battery cells 5 in the battery module 4 can be electrically connected through a busbar component to realize the series connection, parallel connection, or mixed connection of the multiple battery cells 5 in the battery module 4. In the battery module 4, the multiple battery cells 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other manner. Further, the multiple battery cells 5 can be fixed by fasteners.
[0157] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0158] Figure 5 and Figure 6 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The plurality of battery modules 4 in the battery pack 1 may be electrically connected through a busbar component to achieve series connection, parallel connection, or mixed connection of the plurality of battery modules 4 in the battery pack 1. The box body includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0159] Electrical devices
[0160] The embodiment of the present application also provides an electric device, the electric device includes a battery cell provided in the embodiment of the present application, and the battery cell is used to provide electrical energy. The battery cell can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0161] As the electrical device, a battery cell, a battery module including a plurality of battery cells, or a battery pack may be selected according to its usage requirements.
[0162] Figure 7The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the power consumption device for high power and high energy density, a battery pack or a battery module can be used.
[0163] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.
[0164] Example
[0165] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0166] Example 1
[0167] Preparation of positive electrode
[0168] Nickel salt nickel acetate with a volume distribution particle size Dv50 of 200nm was mixed with a water-based binder PVDF and a conductive agent Ketjen black to prepare nickel salt solutions with molar concentrations of Ni element of 0.6mol / L, 0.45mol / L, 0.35mol / L, 0.25mol / L, 0.15mol / L and 0.05mol / L, respectively. For nickel salt solutions with different molar concentrations of Ni element, the molar concentration of the water-based binder was 0.05mol / L, and the concentration of the conductive agent was 0.05mol / L.
[0169] The initial cathode particles LiNi 0.9 Co 0.05 Mn 0.05 (NCM9055), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed evenly in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1.5:2 to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the initial positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes. The compacted density of the positive electrode film layer of the initial positive electrode sheet is 3.5g / cm 3 .
[0170] The initial positive electrode sheet was immersed in a nickel salt solution with a molar concentration of Ni element of 0.6 mol / L for 6 hours. After the immersion, it was dried in an oven at 120°C for 2 hours. This was the first immersion. The initial positive electrode sheet was immersed in 0.45 mol / L, 0.35 mol / L, 0.25 mol / L, 0.15 mol / L, and 0.05 mol / L nickel salt solutions in turn, repeating the same steps as the first immersion to complete the second to sixth immersions to obtain a positive electrode sheet. Among them, the molar concentration of Ni element in the nickel salt solution used for the i-th immersion is recorded as c i mol / L, i is 1, 2, 3, 4, 5 or 6.
[0171] Preparation of negative electrode
[0172] The negative electrode active material artificial graphite, silicon oxide, conductive agent acetylene black, binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 90:5:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0173] Preparation of isolation membrane
[0174] A polyethylene film is used as the isolation film.
[0175] Preparation of electrolyte
[0176] Lithium salt (LiPF 6 The electrolyte is prepared by mixing LiFSI with Li in a mass ratio of 2:8 and dissolving it in a solvent prepared by ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0177] Preparation of secondary batteries
[0178] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a secondary battery is obtained.
[0179] Embodiments 2-11, 13-14
[0180] Based on the preparation process of the positive electrode sheet in Example 1, the preparation parameters such as the type of initial positive electrode particles, the type of nickel salt, the volume distribution particle size Dv50 of the nickel salt particles, the number of impregnations, etc. were adjusted as shown in Table 1 to prepare the positive electrode sheets of Examples 2-11 and 13-14.
[0181] The preparation of the negative electrode sheets, separators, electrolytes and secondary batteries of Examples 2-11, 13-14 is the same as that of Example 1.
[0182] Example 12
[0183] Based on the preparation process of the positive electrode sheet in Example 1, an initial positive electrode sheet was prepared.
[0184] The initial positive electrode sheet was immersed in a nickel acetate solution with a molar concentration of 0.6 mol / L of Ni element for 6 hours. After the immersion, it was dried in an oven at 120°C for 2 hours. This was the first immersion. Subsequently, the initial positive electrode sheet was immersed in a mixed solution of nickel acetate and nickel silicate with a molar concentration of 0.3 mol / L of Ni element (the molar ratio of nickel acetate and nickel silicate was 1:1) for 6 hours. After the immersion, it was dried in an oven at 120°C for 2 hours. Finally, the initial positive electrode sheet was immersed in a mixed solution of nickel acetate, nickel silicate and nickel sulfate with a molar concentration of 0.15 mol / L of Ni element (the molar ratio of nickel acetate, nickel silicate and nickel sulfate was 1:1:1) for 6 hours. After the immersion, it was dried in an oven at 120°C for 2 hours to obtain a positive electrode sheet.
[0185] The preparation of the negative electrode plate, isolation membrane, electrolyte and secondary battery of Example 12 is the same as that of Example 1.
[0186] Comparative Examples 1-3
[0187] Based on the preparation process of the initial positive electrode sheet in Example 1, the positive electrode sheets of Comparative Examples 1-3 were prepared. The initial positive electrode particles of Comparative Example 1 were LiNi 0.9 Co 0.05 Mn 0.05 (NCM9055); the initial positive electrode particles of Comparative Example 2 are LiNi 0.8 Co 0.1 Mn 0.1 (NCM811); the initial positive electrode particles of Comparative Example 3 are LiNi 0.7 Co 0.2 Mn 0.1 (NCM721).
[0188] The preparation of the negative electrode sheets, separators, electrolytes and secondary batteries of Comparative Examples 1-3 is the same as that of Example 1.
[0189] Test Section
[0190] Cyclic performance test
[0191] At 25°C, let the secondary battery stand for 5 minutes, then charge it to 4.25V at a constant current rate of 0.33C (where 1C means the current value corresponding to the complete discharge of the battery's theoretical capacity within 1 hour), then charge it to a cutoff current of 0.05C at a constant voltage of 4.25V, let it stand for 5 minutes, and discharge it to 2.8V at a constant current rate of 0.5C, let it stand for 5 minutes. This is a charge and discharge cycle. Repeat the above steps for the same secondary battery and record the discharge capacity D of the first cycle. 0 And the discharge capacity D at the 1000th cycle 1000 . Cycle capacity retention rate P of secondary battery 1000 =D 1000 / D 0 ×100%.
[0192] The test results are shown in Table 2.
[0193] Table 1
[0194] Serial number Initial cathode particles Nickel salts <![CDATA[c 1 ]]> <![CDATA[c 2 ]]> <![CDATA[c 3 ]]> <![CDATA[c 4 ]]> <![CDATA[c 5 ]]> <![CDATA[c 6 ]]> Nickel salt Dv50 Example 1 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 200nm Example 2 NCM9055 Nickel silicate 0.6 0.45 0.35 0.25 0.15 0.05 200nm Example 3 NCM9055 Nickel carbonate 0.6 0.45 0.35 0.25 0.15 0.05 200nm Example 4 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 0.15 / 200nm Example 5 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 / / 200nm Example 6 NCM9055 Nickel acetate 0.6 0.45 0.35 / / / 200nm Example 7 NCM9055 Nickel acetate 0.6 0.45 / / / / 200nm Example 8 NCM9055 Nickel acetate 0.6 / / / / / 200nm Example 9 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 50nm Example 10 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 100nm Embodiment 11 NCM9055 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 500nm Example 12 NCM9055 Mixed Nickel Salts 0.6 0.3 0.15 / / / 200nm Embodiment 13 NCM811 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 200nm Embodiment 14 NCM721 Nickel acetate 0.6 0.45 0.35 0.25 0.15 0.05 200nm Comparative Example 1 NCM9055 / / / / / / / / Comparative Example 2 NCM811 / / / / / / / / Comparative Example 3 NCM721 / / / / / / / /
[0195] Table 2
[0196] Table 2-1
[0197] Serial number Coating thickness <![CDATA[Electrode sheet compaction g / cm 3 > Cycle performance Example 1 900nm 4.10 90.56% Example 2 900nm 4.10 89.87% Example 3 900nm 4.10 90.46% Example 4 800nm 4.05 90.42% Example 5 700nm 3.95 89.45% Example 6 500nm 3.80 88.79% Example 7 300nm 3.60 88.12% Example 8 200nm 3.55 87.76% Example 9 900nm 4.10 92.23% Example 10 900nm 4.10 91.86% Embodiment 11 900nm 4.10 90.35% Example 12 400nm 3.70 91.77% Comparative Example 1 / 3.50 87.55%
[0198] Table 2-2
[0199] Serial number Coating thickness <![CDATA[The compaction density of the electrode sheet g / cm 3 > Cycle performance Embodiment 13 900nm 4.10 91.54% Embodiment 14 900nm 4.10 93.25% Comparative Example 2 / 3.50 89.65% Comparative Example 3 / 3.50 91.56%
[0200] It can be seen from the test results of Table 1 and Table 2 that the positive electrode plate of the embodiment of the present application includes a specific positive electrode active material, which has a specific structure and composition and can have high stability during the charge and discharge cycle of the battery. Therefore, the positive electrode plate of the embodiment of the present application is applied to a secondary battery, which can effectively improve the cycle performance of the battery.
[0201] In contrast, the positive electrode plate of Comparative Example 1 includes conventional ternary positive electrode material NCM9055, and the cycle performance of its secondary battery is much lower than that of Examples 1 to 12. The positive electrode plate of Comparative Example 2 includes conventional ternary positive electrode material NCM811, and the cycle performance of its secondary battery is much lower than that of Example 13. The positive electrode plate of Comparative Example 3 includes conventional ternary positive electrode material NCM721, and the cycle performance of its secondary battery is much lower than that of Example 14.
[0202] For some compounds given but not listed in the embodiments, since their chemical properties and reaction properties when participating in electrochemical reactions are similar to those of the compounds listed in the embodiments, they are all suitable for the technical scheme of the present invention and are therefore not listed one by one here.
[0203] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode sheet, comprising a positive electrode active material; The positive electrode active material comprises: A core, comprising a nickel-containing lithium transition metal oxide, wherein the molar ratio of the Ni element is greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide; and The coating layer is coated on at least a portion of the surface of the core, and the coating layer includes nickel salt particles.
2. The positive electrode sheet according to claim 1, wherein: Based on the total mass of the core, the mass percentage of the Ni element in the core is w1%; based on the total mass of the coating layer, the mass percentage of the Ni element in the coating layer is w2%; The positive electrode active material satisfies: w2<w1.
3. The positive electrode sheet according to claim 1 or 2, wherein: The coating layer includes a plurality of nickel salt particle layers stacked and distributed in a direction away from the core; Optionally, among the multiple nickel salt particle layers, the mass percentage of Ni element in the nickel salt particle layer far away from the core is less than the mass percentage of Ni element in the nickel salt particle layer close to the core.
4. The positive electrode sheet according to any one of claims 1 to 3, wherein: The coating layer has a thickness of 100 nm to 5 μm, and can be optionally 200 nm to 900 nm; and / or The volume distribution particle size Dv50 of the inner core is 1.2 μm-15 μm, and can be optionally 10 μm-15 μm.
5. The composite cathode material according to any one of claims 1 to 4, wherein The volume distribution particle size Dv50 of the nickel salt particles is 50nm-500nm, and can be optionally 50nm-200nm.
6. The positive electrode sheet according to any one of claims 1 to 5, wherein: The nickel-containing lithium transition metal oxide includes LiNi x Co y Mn z O2, wherein 0.7≤x<1.0, 0<y<0.3, 0<z<0.
3.
7. The positive electrode sheet according to any one of claims 1 to 6, wherein: The nickel salt particles include an oxyacid salt of nickel; Optionally, the nickel salt particles include at least one of nickel acetate, nickel silicate or nickel carbonate.
8. The positive electrode sheet according to any one of claims 1 to 7, wherein: The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, and the positive electrode active material is distributed in the positive electrode film layer; The compaction density of the positive electrode film is greater than or equal to 3.6 g / cm 3 , optional 3.6g / cm 3 -4.6g / cm 3 .
9. A method for preparing a positive electrode sheet, comprising: Providing an initial positive electrode sheet, the initial positive electrode sheet comprising initial positive electrode particles, the initial positive electrode particles comprising a lithium transition metal oxide containing nickel, wherein the molar number of the Ni element accounts for greater than or equal to 0.7 based on the total molar number of transition metal elements in the lithium transition metal oxide containing nickel; The initial positive electrode sheet is immersed in a nickel salt solution and dried to form a coating layer including nickel salt particles on at least a portion of the surface of the initial positive electrode particles to obtain a positive electrode sheet. The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes: A core, comprising a nickel-containing lithium transition metal oxide, wherein the molar ratio of the Ni element is greater than or equal to 0.7 based on the total molar number of transition metal elements in the nickel-containing lithium transition metal oxide; and The coating layer is coated on at least a portion of the surface of the core, and the coating layer includes nickel salt particles.
10. The method according to claim 9, wherein: The step of immersing the initial positive electrode sheet in a nickel salt solution and drying the same comprises: Sequentially immersing the initial positive electrode sheet in a plurality of nickel salt solutions and drying the solutions to form a plurality of stacked nickel salt particle layers on at least a portion of the surface of the initial positive electrode particles; Optionally, in the plurality of nickel salt solutions, the mass percentage of the Ni element decreases in sequence based on the total mass of the solid components in the nickel salt solutions.
11. The method according to claim 9 or 10, wherein: The molar concentration of the Ni element in the nickel salt solution is 0.05 mol / L-0.6 mol / L; and / or Based on the total mass of the solid components in the nickel salt solution, the mass percentage of the Ni element is 5%-60%.
12. The method according to any one of claims 9 to 11, wherein: In the nickel salt solution, the solid component includes nickel salt and optional additives; Optionally, the optional additives include a binder and / or a conductive agent; More optionally, the binder includes an aqueous binder; and the conductive agent includes a conductive carbon material.
13. The method according to any one of claims 9 to 12, wherein: The initial positive electrode sheet includes a positive electrode current collector and an initial positive electrode film layer located on at least one side of the positive electrode current collector, and the compaction density of the initial positive electrode film layer is 3.1 g / cm 3 -4.1g / cm 3 .
14. A battery comprising a positive electrode sheet according to any one of claims 1 to 8, or a positive electrode sheet prepared by the method according to any one of claims 9 to 13.
15. The battery according to claim 14, wherein The battery further comprises an electrolyte, wherein the ionic conductivity of the electrolyte at 25° C. is greater than 10 mS / cm, and can be selected to be 10 mS / cm-18 mS / cm.
16. An electrical device comprising the battery according to claim 14 or 15.
Citation Information
Patent Citations
Lithium secondary battery positive electrode active material, method for preparing same, and lithium secondary battery positive electrode and lithium secondary battery comprising same
CN110809831A
Lithium-rich electrode material, positive pole piece and secondary battery
CN115347154A
Preparation method of positive electrode material with coating layer, lithium battery and electric vehicle
CN115394981A